Experimentations on the retrofitting of damaged Single Step Joints with Self-Tapping Screws - Verbist, Maxime Paul Augustin (2018)
When assessing the roof of existing buildings, engineers may be confronted with structural joints badly preserved, for instance the damaged Single Step Joint (SSJ) located at the foot of timber trusses. Since the early appearance of failure modes in this traditional carpentry connection may lead to the collapse of the whole timber truss, the retrofitting of damaged SSJ is then required as an economically-viable intervention to stabilize the roof structure. In consequence, the retrofitting of damaged SSJ with Self-Tapping Screws (STS) has been conducted through the Experimental Campaign in order to explore further different possibilities offered by this recent intervention technique (Sobra et al. (2016)). To this end, two strategies, noted R1 and R2, have been proposed to retrofit the SSJ specimens with STS, which had been previously damaged due to both failure modes, namely the crushing at the front-notch surface and the shear crack in the tie beam (Verbist et al. (2017)). Afterwards, the SSJ specimens retrofitted with STS have been tested under monotonic compression in the rafter in order to pull out their mechanical behaviour encompassing the failure modes, the force-displacement response, the stiffness of the connection, and the ultimate normal force in the rafter. By comparing the mechanical behaviour of retrofitted SSJ specimens with the initial ones from Verbist et al. (2017), the performances of both retrofitting strategies with STS have been discussed. Furthermore, the impact of the shear row splitting on the mechanical behaviour of retrofitted SSJ has been evaluated, by providing some warnings to engineers when intervening in existing timber trusses featuring natural damage such as the shrinkage splitting.